Achieving Gold in Cambridge Lower Secondary Science Test - Munawwarah Munawwarah; Zulqifli Alqadri (Postgraduate, University of Mataram, 2023)
This study investigates students’ performance in the Cambridge Lower Secondary Test, especially in science subjects, after implementing the AIR (Auditory, Intellectually, and Repetition) learning model. The research subjects are ICP (International Class Program), totaling 16 students at SMP IT Albiruni Mandiri Makassar. The implementation of the AIR model is carried out since students are in stage 8 and continue to stage 9. The type of test for stages 7 and 8 is the Cambridge Lower Secondary Progression Test. The stage 9 test type is the Cambridge Lower Secondary Checkpoint. The test results are described in the form of grades, namely Bronze, Silver, and Gold. At stage 7, the percentage of students who received Bronze was 68.75%, Silver 31.25%, and Gold 0.00%. There was a significant increase in stage 8, with 37.50% who got Bronze, 18.75% got Silver, and 43.75% got Gold. Then at stage 9, there was an increase of 68.75% of students who got Gold, 12.50% got Silver, and 18.75% got Bronze